The Tao of Wu - RZA 1969- (Riverhead Books, 2010)
Autobiography of "RZA, founder of the Wu-Tang Clan and hip-hop's most exalted wise man"--Front cover jacket
Keywords: RZA -- 1969-; Wu-Tang Clan -- Musikgruppe; Rap; Rapmusiker; RZA / (Rapper); Wu-Tang Clan (Musical group); Rap musicians / United States / Biography; Sound recording executives and producers / United States / Biography; Rap (Music) / History and criticism; Spirituality in music; Music and philosophy; Spiritualité dans la musique; Musique et philosophie; RZA / (Rapper) / https://id.oclc.org/worldcat/entity/E39PBJtrR9dMGmQB7kXJhgjV4q; Rap (Music); Rap musicians; Sound recording executives and producers; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; RZA.; Biographies; Criticism, interpretation, etc; Autobiografie